2012
DOI: 10.1016/j.jtbi.2012.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic time in quasispecies evolution

Abstract: a b s t r a c tThe time a phenotype takes to achieve a stationary state from an initial condition depends on multiple factors. In particular, it is a function of both its fitness and its mutation rate. We evaluate the average time, referred to as the characteristic time, T c , that the system takes to reach a final steady state of simple models of populations formed by self-replicative sequences. The dependence of T c on the mutation rate and on the fitness landscape is also studied. For simple fitness landsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…As before, and . As it can be observed, the curves for large values of are qualitatively similar, all exhibiting a minimum value for approximately the same mutation rate and a relative maximum near the error catastrophe (an extended description of this behavior has been previously presented in [15]). Note that as the amplification factor decreases, the curves move to the left and to higher values of .…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…As before, and . As it can be observed, the curves for large values of are qualitatively similar, all exhibiting a minimum value for approximately the same mutation rate and a relative maximum near the error catastrophe (an extended description of this behavior has been previously presented in [15]). Note that as the amplification factor decreases, the curves move to the left and to higher values of .…”
Section: Resultssupporting
confidence: 69%
“…In addition, this fitness degeneracy is partly responsible for the strong discrepancy with the deterministic outcome. The effect of ruggedness on the characteristic time has already been studied in a previous paper [15]. In that paper we studied the characteristic time of a population of replicators in more rugged landscapes, namely multiplicative with two peaks, binary rugged and Kauffman-NK landscapes, and showed that it presents a similar dependence on the mutation rate.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations